Can we save planet earth? - Films For The Humanities & Sciences (Firm); The Open University (Princeton, N.J. : Films for the Humanities & Sciences, 2008)
Due to global warming, Earth is hovering at the climatic tipping point. After summarizing the state of greenhouse gas emissions and predicting future weather changes with climate modeling, this program presented by Sir David Attenborough circles the globe to create a composite picture of burgeoning eco-disaster: extended droughts, devastating flash floods, stronger hurricanes, unpredictable wildfires, species extinctions, melting ice caps, acidified oceans, food chain failure, and rising sea levels. A composite solution involving reduced-carbon living, carbon-free power sources, and geological carbon dioxide sequestration is brought forward as well-and concerted implementation must begin now
Presenter: Sir David Attenborough
Keywords: Climate changes; Climatic changes -- Environmental aspects; Global environmental change